Coated ultra-high molecular weight polyethylene fiber as well as preparation method and application thereof

By designing a porous structure for ultra-high molecular weight polyethylene fibers and filling them with wave absorbing resin and fillers, the wave transmission problem caused by its small dielectric constant is solved, and the wave absorbing stealth function and excellent performance of composite materials are achieved.

CN119593213APending Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311153962.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Ultra-high molecular weight polyethylene fiber has a small dielectric constant and is easy to transmit waves, which limits its application in wave absorbing stealth materials.

Method used

Improve its absorbing stealth performance by designing a porous structure for ultra-high molecular weight polyethylene fibers, increasing interfacial composite properties, and filling fiber surfaces and holes with absorbing resins and fillers, such as nano-iron powder or graphene particles.

Benefits of technology

It realizes the absorbing stealth function of ultra-high molecular weight polyethylene fibers, and can be combined with other high-performance fibers to make absorbing stealth composite materials. It has excellent absorption radar wave performance, while maintaining lightweight, high strength and good toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004437879310000181
    Figure BDA0004437879310000181
Patent Text Reader

Abstract

The invention relates to a coated ultra-high molecular weight polyethylene fiber as well as a preparation method and application thereof. The coated ultra-high molecular weight polyethylene fiber comprises a porous fiber matrix and a coating material, wherein the coating material coats at least one part of the surface of the fiber matrix and is filled in at least one part of holes of the fiber matrix, and the porosity of the porous fiber matrix is 5-40%. The fiber provided by the invention can be prepared into a wave-absorbing stealth composite material with high-performance fibers such as carbon fibers, glass fibers, aramid fibers and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high-performance fibers, and in particular to a coated ultra-high molecular weight polyethylene fiber, a manufacturing method thereof and applications thereof. Background Art

[0002] Ultra-high molecular weight polyethylene fiber has many advantages such as high strength, fatigue resistance, chemical corrosion resistance, etc. It has been widely used in military bulletproof, marine fishery and other fields. It is also a very important reinforcing skeleton material in radar-absorbing shielding. However, because ultra-high molecular weight polyethylene fiber has a small dielectric constant and is easy to transmit waves, its application in radar-absorbing stealth materials is limited. Summary of the invention

[0003] The present invention provides an ultra-high molecular weight polyethylene fiber with radar absorbing and stealth functions. The fiber has a hole structure and high interface compositeness. The fiber is coated with a radar absorbing resin to impart radar absorbing and stealth performance. The fiber provided by the present invention can be made into radar absorbing and stealth composite materials with high-performance fibers such as carbon fiber, glass fiber, and aramid. The composite materials have excellent radar wave absorbing performance and are also characterized by light weight, high strength, and good toughness.

[0004] Specifically, the present invention relates to the following aspects.

[0005] 1. A coated ultra-high molecular weight polyethylene fiber, comprising a porous fiber matrix and a coating material that covers at least a portion of the surface of the fiber matrix and fills at least a portion of the holes in the fiber matrix, wherein the porosity of the porous fiber matrix is ​​5-40% (preferably 10-20%).

[0006] 2. The coated ultra-high molecular weight polyethylene fiber according to any one of the preceding or following aspects, wherein the coating material comprises a filler and a resin.

[0007] 3. The coated ultra-high molecular weight polyethylene fiber described in any of the preceding or following aspects, wherein the filler is selected from at least one of metal particles, metal oxide particles, ceramic particles, conductive polymer particles, nanofibers and graphene particles, preferably selected from at least one of nano iron powder and graphene particles, and its average particle size is 1-100nm (preferably 20-50nm), and / or the resin is selected from at least one of thermosetting resins and thermoplastic resins, preferably selected from at least one of epoxy resins, unsaturated polyester resins, phenolic resin rubber, polyurethane, nylon resin, polystyrene resin, methacrylic resin and vinyl ester resin, particularly preferably selected from at least one of epoxy resins and polyurethanes.

[0008] 4. The coated ultra-high molecular weight polyethylene fiber described in any of the preceding or following aspects, wherein the weight of the filler is 1-60 (preferably 20-30) parts relative to 100 parts by weight of the resin, or, relative to 100 parts by weight of the coated ultra-high molecular weight polyethylene fiber, the weight of the filler is 0.1-20 (preferably 0.3-3) parts.

[0009] 5. The coated ultra-high molecular weight polyethylene fiber described in any of the above or the following aspects, wherein the viscosity-average molecular weight of the ultra-high molecular weight polyethylene constituting the fiber matrix is ​​1 million to 9 million (preferably 3 million to 5 million).

[0010] 6. A method for producing a coated ultra-high molecular weight polyethylene fiber, comprising the following steps:

[0011] 1) producing a porous ultra-high molecular weight polyethylene fiber, wherein the porosity of the porous ultra-high molecular weight polyethylene fiber is 5-40% (preferably 10-20%),

[0012] 2) The porous ultra-high molecular weight polyethylene fiber is immersed in a coating bath and then dried and solidified to obtain the coated ultra-high molecular weight polyethylene fiber.

[0013] 7. The manufacturing method according to any one of the preceding or following aspects, wherein the step 1) comprises the following steps:

[0014] 1-1) ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent are mixed to prepare a spinning solution,

[0015] 1-2) extruding the spinning solution to form a spinning fine stream,

[0016] 1-3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers,

[0017] 1-4) stretching the dry raw yarn in one or more stages (such as 2-10 or 2-6 stages) to obtain pre-drawn yarn,

[0018] 1-5) The pre-drawn filaments are immersed in an acid bath under ultrasonic or non-ultrasonic conditions to dissolve the acid-soluble inorganic particles, thereby obtaining the porous ultra-high molecular weight polyethylene fibers.

[0019] 8. The manufacturing method described in any of the preceding or following aspects, wherein in step 1-1), the amount of the acid-soluble inorganic particles used is 0.5-50 parts by weight (preferably 1-10 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene, and the amount of the solvent used is 100-3000 parts by weight (preferably 400-2000 parts by weight).

[0020] 9. The production method described in any of the preceding or following aspects, wherein in step 1-1), the solvent is selected from at least one of naphthalene, decalin, tetralin, kerosene, xylene, toluene, petroleum fractions, halogenated hydrocarbons, cycloalkanes, and cycloolefins, preferably decalin.

[0021] 10. The production method described in any one of the preceding or following aspects, wherein in step 1-1), the average particle size of the acid-soluble inorganic particles is 0.02-20 μm (preferably 0.5-5 μm).

[0022] 11. The manufacturing method described in any of the preceding or following aspects, wherein in step 1-1), the acid-soluble inorganic particles are selected from at least one particle of calcium carbonate, sodium carbonate, sodium bicarbonate, and magnesium carbonate (preferably calcium carbonate particles, especially light calcium carbonate particles).

[0023] 12. The method of any one of the preceding or following aspects, wherein in step 1-1), the difference between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.10 g / cm 3 Above (preferably 0.25-0.60g / cm 3 ).

[0024] 13. The manufacturing method described in any of the above or the following aspects, wherein in step 1-1), the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 9 million (preferably 3 million to 5 million).

[0025] 14. The manufacturing method described in any one of the preceding or following aspects, wherein in step 1-1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.

[0026] 15. The manufacturing method described in any of the above or the following aspects, wherein in step 1-2), stretching exists or does not exist, and the extrusion temperature is 150-250°C (preferably 170-190°C); when stretching exists, the stretching ratio is 0-50 (preferably 2-20).

[0027] 16. The manufacturing method according to any one of the preceding or following aspects, wherein in step 1-3), the spinning stream is cooled to obtain gel filaments, and then at least a portion of the solvent is removed by evaporation and / or extraction.

[0028] 17. The manufacturing method described in any of the above or the following aspects, wherein the cooling operating conditions include: with or without stretching, the cooling temperature is -50-100°C (preferably 20-50°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5).

[0029] 18. The manufacturing method described in any of the above or below aspects, wherein the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature; when stretching is present, the stretching ratio is 1-10 (preferably 2-5), or, the operating conditions of the extraction include: with or without stretching, the extractant is a volatile hydrocarbon solvent (preferably selected from at least one of xylene and heptane), the extraction temperature is 10-150°C (preferably 40-90°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5).

[0030] 19. The manufacturing method described in any of the preceding or following aspects, wherein in step 1-4), the stretching operating conditions include: 1-10 stretching sections (preferably 2-5), a stretching temperature of 90-170°C (preferably 130-150°C), and a stretching ratio of 2-500 (preferably 4-250).

[0031] 20. The manufacturing method described in any of the preceding or following aspects, wherein in step 1-4), the dry raw silk is first pre-stretched, and then the dry raw silk is further stretched (called post-stretching) in one or more (such as 1-9 or 1-5) stages, and the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio of the post-stretching (total) is 2-50 (preferably 5-20).

[0032] 21. The manufacturing method described in any of the above or the following aspects, wherein there is no stretching during the process of step 1-5), or there is no stretching operation after the step 1-5) is completed.

[0033] 22. The production method according to any one of the preceding or following aspects, wherein in step 1-5), the acidic bath comprises at least one acid selected from inorganic acids and organic acids, and a solvent.

[0034] 23. The manufacturing method described in any of the preceding or following aspects, wherein the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid, and phosphoric acid (preferably selected from at least one of sulfuric acid and hydrochloric acid), the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid (preferably selected from at least one of acetic acid and citric acid), and the solvent is selected from at least one of glacial acetic acid, ethanol, and water, preferably water.

[0035] 24. The production method according to any one of the preceding or following aspects, wherein the pH value of the acidic bath is ≤ 6 (preferably 2-3).

[0036] 25. The manufacturing method described in any of the above or the following aspects, wherein in step 1-5), the dissolution operating conditions include: the dissolution temperature is 0-80°C (preferably 20-40°C), the dissolution time is 0.5-60min (preferably 10-20min), and when there is ultrasonic oscillation, the frequency is 10-70Hz (preferably 30-40Hz).

[0037] 26. The manufacturing method described in any of the preceding or following aspects, wherein in step 1-4), an oil is applied to the dry raw silk before the stretching is performed and / or between any two stages.

[0038] 27. The manufacturing method described in any of the preceding or following aspects, wherein in step 1-4), an oil is applied to the dry raw silk before the post-stretching is performed and / or between any two stages (if any) of the post-stretching.

[0039] 28. The production method described in any of the above or below aspects, wherein the oil agent is selected from at least one of glycerides, mineral oils, lauryl alcohol polyoxyethylene ethers, and antistatic agents, preferably glycerides.

[0040] 29. The production method described in any of the preceding or following aspects, wherein the amount of the oil agent used is 0-10% (preferably 0.1-3%).

[0041] 30. The manufacturing method according to any one of the preceding or following aspects, wherein in step 2), the coating bath comprises a filler, a resin and a dispersion medium.

[0042] 31. The manufacturing method described in any of the preceding or following aspects, wherein the weight parts of the filler are 1-60 (preferably 20-30) and the weight parts of the dispersion medium are 1-10 (preferably 2-5) relative to 100 weight parts of the resin.

[0043] 32. The manufacturing method described in any of the above or the following aspects, wherein the filler is selected from at least one of metal particles, metal oxide particles, ceramic particles, conductive polymer particles, nanofibers and graphene particles, and its average particle size is 1-100nm (preferably 20-50nm), the resin is selected from at least one of thermosetting resins and thermoplastic resins, preferably selected from at least one of epoxy resins, unsaturated polyester resins, phenolic resin rubber, polyurethane, nylon resin, polystyrene resin, methacrylic resin and vinyl ester resin, and the dispersion medium is selected from at least one of lipids, low molecular waxes, and metal soaps, preferably selected from at least one of stearamide, paraffin, and calcium stearate.

[0044] 33. The manufacturing method described in any of the above or the following aspects, wherein in step 2), the operating conditions of the impregnation include: using tension porcelain pieces, under ultrasonic oscillation, the oscillation frequency is 10-70Hz (preferably 30-40Hz), the oscillation time is 1-120min (preferably 10-30min), the impregnation temperature is 0-100℃ (preferably 40-60℃), the impregnation time is 1-120min (preferably 10-30min), and the coating amount is 0.1%-30% (preferably 2%-5%).

[0045] 34. The manufacturing method described in any of the above or the following aspects, wherein in step 2), the operating conditions of the drying include: a drying temperature of 40-150°C (preferably 60-80°C) and a drying time of 10-180 min (preferably 30-60 min).

[0046] 35. The manufacturing method according to any one of the preceding or following aspects, wherein in step 1-3), at least a portion of the solvent is removed from the spinning stream by evaporation.

[0047] 36. The manufacturing method described in any of the above or the following aspects, wherein in step 1-3), the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature; when stretching is present, the stretching ratio is 1-10 (preferably 2-5).

[0048] 37. A fabric comprising the coated ultra-high molecular weight polyethylene fiber described in any one of the preceding or following aspects.

[0049] 38. A wave-absorbing composite sheet, comprising the coated ultra-high molecular weight polyethylene fiber described in any one of the preceding or following aspects.

[0050] 39. The fabric or microwave-absorbing composite sheet described in any of the preceding or following aspects further comprises at least one other fiber selected from natural plant fibers, natural animal fibers, artificial regenerated fibers, synthetic fibers and inorganic fibers.

[0051] Technical Effects

[0052] The fiber belt of the present invention has a hole structure and high interface compositeness, which solves the problem that ultra-high molecular weight fibers are difficult to composite. The ultra-high molecular weight polyethylene fiber has a hole structure, which greatly improves the interface compositeness. The ultra-high molecular weight polyethylene fiber with a hole structure is coated in a resin containing an oil-containing absorbent to perform wave-absorbing stealth modification. The modified ultra-high molecular weight polyethylene fiber can be composited with carbon fiber, glass fiber, and aramid to form a wave-absorbing stealth composite material. At the same time, the fiber is coated with a wave-absorbing resin to make the ultra-high molecular weight polyethylene fiber have wave-absorbing stealth performance, which can be directly pressed into a composite sheet or composited with other sheets. DETAILED DESCRIPTION

[0053] The specific embodiments of the present invention are described in detail below, but it should be pointed out that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims in the appendix.

[0054] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.

[0055] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0056] In the context of the present invention, all numerical values ​​for parameters (eg amounts or conditions) are to be understood as being modified in all instances by the term "about", regardless of whether "about" actually appears before the numerical value.

[0057] In the context of the present invention, the method of measuring porosity is mercury porosimetry.

[0058] In the context of the present invention, the method of measuring the average particle size is laser light scattering.

[0059] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight and pressure is gauge pressure.

[0060] In the context of the present invention, any two or more embodiments or aspects of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0061] According to one embodiment of the present invention, a coated ultra-high molecular weight polyethylene fiber is provided, comprising a porous fiber matrix and a coating material that covers at least a portion of the surface of the fiber matrix and fills at least a portion of the pores of the fiber matrix.

[0062] According to one embodiment of the present invention, the porosity of the porous fiber matrix is ​​5-40% (preferably 10-20%). A porosity within a reasonable range can maintain the advantages of light weight and high strength of the fiber, while having sufficient adsorption and bonding properties to meet the requirements of wave absorption modification.

[0063] According to one embodiment of the present invention, the coating material comprises a filler and a resin.

[0064] According to one embodiment of the present invention, the filler is selected from at least one of metal particles, metal oxide particles, ceramic particles, conductive polymer particles, nanofibers and graphene particles, preferably selected from at least one of nano iron powder and graphene particles.

[0065] According to one embodiment of the present invention, the average particle size is 1-100 nm (preferably 20-50 nm).

[0066] According to one embodiment of the present invention, the resin is selected from at least one of a thermosetting resin and a thermoplastic resin, preferably selected from at least one of an epoxy resin, an unsaturated polyester resin, a phenolic resin rubber, a polyurethane, a nylon resin, a polystyrene resin, a methacrylic resin and a vinyl ester resin, and particularly preferably selected from at least one of an epoxy resin and a polyurethane.

[0067] According to one embodiment of the present invention, the weight portion of the filler is 1-60 (preferably 20-30) relative to 100 parts by weight of the resin.

[0068] According to one embodiment of the present invention, the weight portion of the filler is 0.1-20 (preferably 0.3-3) relative to 100 parts by weight of the coated ultra-high molecular weight polyethylene fiber.

[0069] According to one embodiment of the present invention, the viscosity-average molecular weight of the ultra-high molecular weight polyethylene constituting the fiber matrix is ​​1 million to 9 million (preferably 3 million to 5 million).

[0070] According to one embodiment of the present invention, a method for manufacturing a coated ultra-high molecular weight polyethylene fiber is also provided, comprising the following steps:

[0071] 1) Manufacturing porous ultra-high molecular weight polyethylene fibers,

[0072] 2) The porous ultra-high molecular weight polyethylene fiber is immersed in a coating bath and then dried and solidified to obtain the coated ultra-high molecular weight polyethylene fiber.

[0073] According to the present invention, the porosity of the porous ultra-high molecular weight polyethylene fiber is 5-40% (preferably 10-20%).

[0074] According to one embodiment of the present invention, step 1) comprises the following steps:

[0075] 1-1) ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent are mixed to prepare a spinning solution,

[0076] 1-2) extruding the spinning solution to form a spinning fine stream,

[0077] 1-3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers,

[0078] 1-4) stretching the dry raw yarn in one or more stages (such as 2-10 or 2-6 stages) to obtain pre-drawn yarn,

[0079] 1-5) The pre-drawn filaments are immersed in an acid bath under ultrasonic or non-ultrasonic conditions to dissolve the acid-soluble inorganic particles, thereby obtaining the porous ultra-high molecular weight polyethylene fibers.

[0080] According to one embodiment of the present invention, in step 1-1), the amount of the acid-soluble inorganic particles is 0.5-50 parts by weight (preferably 1-10 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene.

[0081] According to one embodiment of the present invention, in step 1-1), the amount of the solvent used is 100-3000 parts by weight (preferably 400-2000 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene.

[0082] According to one embodiment of the present invention, in step 1-1), the solvent is selected from at least one of naphthalene, decalin, tetralin, kerosene, xylene, toluene, petroleum fractions, halogenated hydrocarbons, cycloalkanes, and cycloolefins, preferably decalin.

[0083] According to one embodiment of the present invention, in step 1-1), the average particle size of the acid-soluble inorganic particles is 0.02-20 μm (preferably 0.5-5 μm).

[0084] According to one embodiment of the present invention, in step 1-1), the acid-soluble inorganic particles are not particularly limited, and may be any inorganic particles that can react chemically with an acid (especially hydrochloric acid or a hydrochloric acid aqueous solution) to be converted into a (water) soluble compound, and in particular may be at least one particle selected from calcium carbonate, sodium carbonate, sodium bicarbonate and magnesium carbonate, preferably calcium carbonate particles, especially light calcium carbonate particles (whose bulk density is generally 0.50-0.70 g / cm 3 ).

[0085] According to one embodiment of the present invention, in order to make the technical effect of the present invention more excellent, in step 1-1), the difference (absolute value) between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.10 g / cm 3 Above (preferably 0.25-0.60g / cm 3 ). Preferably, the relative density of the ultra-high molecular weight polyethylene is greater than the bulk density of the acid-soluble inorganic particles. It is known that the relative density of the ultra-high molecular weight polyethylene is generally 0.90-0.97 g / cm 3 .

[0086] According to one embodiment of the present invention, in step 1-1), the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 9 million (preferably 3 million to 5 million).

[0087] According to one embodiment of the present invention, in step 1-1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.

[0088] According to one embodiment of the present invention, in step 1-2), stretching is present or absent, and the extrusion temperature is 150-250° C. (preferably 170-190° C.) When stretching is present, the stretching ratio is 0-50 (preferably 2-20).

[0089] According to one embodiment of the present invention, in step 1-3), at least a portion of the solvent is removed from the spinning stream by evaporation (direct evaporation desolvation method). According to the present invention, except for the following clear operating conditions, there is no other limitation on the direct evaporation desolvation method, and it can be carried out in a manner conventionally known in the art. Here, the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature. When stretching is present, the stretching ratio is 1-10 (preferably 2-5).

[0090] According to one embodiment of the present invention, in step 1-3), the spinning stream is cooled to obtain gel filaments (gel spinning method), and then at least a portion of the solvent is removed by evaporation and / or extraction. According to the present invention, except for the following clear operating conditions, there is no other limitation for the gel spinning method, and it can be carried out in a conventional manner known in the art.

[0091] According to one embodiment of the present invention, the cooling operation conditions include: with or without stretching, the cooling temperature is -50-100°C (preferably 20-50°C). When stretching is present, the stretching ratio is 1-10 (preferably 2-5).

[0092] According to one embodiment of the present invention, the evaporation operation conditions include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature. When stretching is present, the stretching ratio is 1-10 (preferably 2-5).

[0093] According to one embodiment of the present invention, the operating conditions of the extraction include: with or without stretching, the extraction temperature is 10-150°C (preferably 40-90°C). When stretching is present, the stretching ratio is 1-10 (preferably 2-5). Here, the extractant is a volatile hydrocarbon solvent, preferably at least one selected from xylene and heptane.

[0094] According to one embodiment of the present invention, in step 1-4), the stretching operating conditions include: 1-10 stretching sections (preferably 2-5), a stretching temperature of 90-170°C (preferably 130-150°C), and a stretching ratio of 2-500 (preferably 4-250).

[0095] According to one embodiment of the present invention, in step 1-4), the dry precursor is pre-stretched first, and then further stretched (referred to as post-stretching) in one or more stages (such as 1-9 or 1-5). Here, the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio (total) of the post-stretching is 2-50 (preferably 5-20).

[0096] According to one embodiment of the present invention, there is no stretching during step 1-5), or there is no stretching operation after step 1-5).

[0097] According to one embodiment of the present invention, in step 1-5), the acid bath comprises at least one acid selected from inorganic acids and organic acids, and a solvent.

[0098] According to one embodiment of the present invention, the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid, and phosphoric acid, preferably selected from at least one of sulfuric acid and hydrochloric acid. In addition, the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid, preferably selected from at least one of acetic acid and citric acid.

[0099] According to one embodiment of the present invention, the solvent is selected from at least one of glacial acetic acid, ethanol and water, preferably water.

[0100] According to one embodiment of the present invention, the pH value of the acidic bath is ≤6 (preferably 2-3).

[0101] According to one embodiment of the present invention, in step 1-5), the dissolution operating conditions include: the dissolution temperature is 0-80°C (preferably 20-40°C), the dissolution time is 0.5-60min (preferably 10-20min), and the frequency is 10-70Hz (preferably 30-40Hz) when ultrasonic oscillation is present.

[0102] According to one embodiment of the present invention, in step 1-4), an oil is applied to the dry raw silk before the stretching and / or between any two stages.

[0103] According to one embodiment of the present invention, in step 1-4), an oil is applied to the dry raw silk before the stretching and / or between any two stages. Alternatively, an oil is applied to the dry raw silk before the post-stretching and / or between any two stages (if any) of the post-stretching. According to the present invention, since the surface of the fiber to which the peracid-soluble inorganic particles are added is rough, it is easy to wear and cause powder loss or fiber surface damage during the subsequent drawing process, and oil film protection is generally required.

[0104] According to one embodiment of the present invention, the oil agent is selected from at least one of glycerides, mineral oils, lauryl alcohol polyoxyethylene ethers, and antistatic agents, preferably glycerides.

[0105] According to one embodiment of the present invention, the amount of the oil agent is 0-10% (preferably 0.1-3%).

[0106] According to one embodiment of the present invention, in step 2), the coating bath comprises a filler, a resin and a dispersion medium.

[0107] According to one embodiment of the present invention, the resin is selected from at least one of thermosetting resins and thermoplastic resins, preferably selected from at least one of epoxy resins, unsaturated polyester resins, phenolic resin rubbers, polyurethanes, nylon resins, polystyrene resins, methacrylic resins and vinyl ester resins.

[0108] According to one embodiment of the present invention, the weight portion of the filler is 1-60 (preferably 20-30) relative to 100 parts by weight of the resin.

[0109] According to one embodiment of the present invention, the filler (particles) is selected from at least one of metal particles, metal oxide particles, ceramic particles, conductive polymer particles, nanofibers and graphene particles. Here, the average particle size of the filler is 1-100nm (preferably 20-50nm).

[0110] According to one embodiment of the present invention, the weight parts of the dispersion medium is 1-10 (preferably 2-5) relative to 100 parts by weight of the resin.

[0111] According to one embodiment of the present invention, the dispersion medium is selected from at least one of lipids, low molecular waxes, and metal soaps, and is preferably selected from at least one of stearamide, paraffin, and calcium stearate.

[0112] According to one embodiment of the present invention, in step 2), the operating conditions of the impregnation include: using tension porcelain, under ultrasonic oscillation, the oscillation frequency is 10-70Hz (preferably 30-40Hz), the oscillation time is 1-120min (preferably 10-30min), the impregnation temperature is 0-100℃ (preferably 40-60℃), the impregnation time is 1-120min (preferably 10-30min), and the coating amount is 0.1%-30% (preferably 2%-5%).

[0113] According to one embodiment of the present invention, in step 2), the drying operation conditions include: a drying temperature of 40-150° C. (preferably 60-80° C.) and a drying time of 10-180 min (preferably 30-60 min).

[0114] According to one embodiment of the present invention, it also relates to a fabric, comprising the coated ultra-high molecular weight polyethylene fiber described in any one of the preceding or following aspects of the present specification.

[0115] According to one embodiment of the present invention, it also relates to an absorbing composite plate material, comprising the coated ultra-high molecular weight polyethylene fiber described in any one of the preceding or following aspects of the present specification.

[0116] According to one embodiment of the present invention, the fabric or the microwave-absorbing composite sheet further comprises at least one other fiber selected from natural plant fibers, natural animal fibers, artificial regenerated fibers, synthetic fibers and inorganic fibers.

[0117] Example

[0118] The present invention is further described in detail below using examples and comparative examples, but the present invention is not limited to these examples.

[0119] Example 1

[0120] The coated ultra-high molecular weight polyethylene fiber of this embodiment is obtained by the following process:

[0121] The acid-soluble inorganic particles are light calcium carbonate, and the difference between the bulk density and the relative density of ultra-high molecular weight polyethylene is 0.4g / cm 3 , the average particle size is 1μm, after being mixed and dispersed evenly with decahydronaphthalene solvent, it is mixed with ultra-high molecular weight polyethylene to form a swelling suspension. The molecular weight of ultra-high molecular weight polyethylene is 4.5 million. The mass ratio of ultra-high molecular weight polyethylene: calcium carbonate: decahydronaphthalene is 100:2:1300. The suspension is sheared and dissolved by a screw, and extruded at 180°C and 8 times stretching to form a spinning fine flow. The direct evaporation and solvent removal method is adopted, the evaporation temperature is 3°C higher than the flash temperature of decahydronaphthalene, and the stretching ratio is 3. This step removes at least 95% of the solvent residue. Then it passes through 3 stretching sections, the stretching temperature is 140-147°C, the stretching ratio is 20, and then it passes through a dilute hydrochloric acid bath (hydrochloric acid and water) with a pH of 3, the stretching ratio in the bath is 1.45, and it is ultrasonically oscillated at 30°C and 30Hz, dissolved for 15 minutes, and then oiled by an oil tanker with an oiling ratio of 0.5%, and finally forms a 400D porous ultra-high molecular weight polyethylene fiber. The porosity was 17.8% as measured by mercury intrusion porosimetry.

[0122] The coating bath is prepared using epoxy resin, the filler is graphene powder, the filler particle size is 30nm, the dispersant is paraffin, and the epoxy resin: graphene: paraffin = 100:25:4. A tension porcelain piece is used, under ultrasonic oscillation, the oscillation frequency is 35Hz, the oscillation time is 20min, the immersion temperature is 50℃, the immersion time is 15min, and the coating amount is 3%. Then it is dried, the drying temperature is 70℃, and the drying time is 40min. The coated ultra-high molecular weight polyethylene fiber is obtained, and the weight part of graphene is 1 relative to 100 weight parts of the coated ultra-high molecular weight polyethylene fiber.

[0123] The coated ultra-high molecular weight polyethylene fiber is alternately mixed with carbon fiber, ceramic fiber, etc. in a certain proportion into yarn bundles, woven into plain cloth and then made into a composite material to achieve good wave absorbing properties.

[0124] Example 2

[0125] Same as Example 1, except that the average particle size of graphene is 100 nm.

[0126] Example 3

[0127] Same as Example 1, except that epoxy resin: graphene: paraffin = 100:60:4.

[0128] Example 4

[0129] Same as Example 1, except that the average particle size of calcium carbonate is 15 μm.

[0130] The porosity of the porous ultra-high molecular weight polyethylene fiber is 25.2%.

[0131] Example 5

[0132] The same as Example 1, except that the calcium carbonate is not premixed with the solvent, but is directly mixed with the ultra-high molecular weight polyethylene and the solvent.

[0133] The porosity of the porous ultra-high molecular weight polyethylene fiber is 4.9%.

[0134] Example 6

[0135] The same as Example 1, except that the filler is ferrite with an average particle size of 45 nm.

[0136] Example 7

[0137] Same as Example 6, except that the coating resin is polyurethane.

[0138] Example 8

[0139] Same as Example 1, except that the coating amount was 0.1%.

[0140] Example 9

[0141] Same as Example 1, except that the coating amount is 25%.

[0142] Example 10

[0143] Same as Example 1, except that the acid-soluble inorganic particles are a mixture of heavy calcium carbonate and light calcium carbonate, and the difference between the bulk density and the relative density of ultra-high molecular weight polyethylene is 0.20 g / cm 3 .

[0144] The porosity of the porous ultra-high molecular weight polyethylene fiber is 7.9%.

[0145] Embodiment 11

[0146] Same as Example 1, except that the acid-soluble inorganic particles are magnesium carbonate, and the difference between its bulk density and the relative density of ultra-high molecular weight polyethylene is 0.65 g / cm 3 .

[0147] The porosity of the porous ultra-high molecular weight polyethylene fiber is 6.3%.

[0148] Example 12

[0149] The same as Example 1, except that the molecular weight of the ultra-high molecular weight polyethylene is 5 million. The mass ratio of ultra-high molecular weight polyethylene: calcium carbonate: decalin is 100:9:1300.

[0150] The porosity of the porous ultra-high molecular weight polyethylene fiber is 19.8%.

[0151] Example 13

[0152] The same as Example 1, except that the evaporation temperature is 5°C higher than the flash evaporation temperature of decalin, the stretching ratio is 5, and this step removes at least 98% of the solvent residue.

[0153] The porosity of the porous ultra-high molecular weight polyethylene fiber is 15.2%.

[0154] Embodiment 14

[0155] The same as Example 1, except that it goes through 5 stretching sections instead of 3 stretching sections, the stretching temperature is 145°C, and the stretching ratio is 20.

[0156] The porosity of the porous ultra-high molecular weight polyethylene fiber is 13.8%.

[0157] Embodiment 15

[0158] Same as Example 1, except that the dispersion medium is calcium stearate, and the ratio of epoxy resin: graphene: paraffin is 100:30:5.

[0159] Comparative Example 1

[0160] The fiber is commercially available LY25 400D ultra-high molecular weight polyethylene fiber, and its porosity is 0.5%.

[0161] Comparative Example 2

[0162] Same as Example 1, except that light calcium carbonate is replaced by sodium chloride.

[0163] The porosity of the porous ultra-high molecular weight polyethylene fiber is 2.5%.

[0164] Comparative Example 3

[0165] The same as Example 1, except that it is first passed through a dilute hydrochloric acid bath (hydrochloric acid prepared with water) with a pH of 3, the stretching ratio in the bath is 1.45, ultrasonic oscillation is performed at 30°C and 30Hz, and the film is dissolved for 15 minutes, and then passed through 3 stretching sections, the stretching temperature is 140-147°C, and the stretching ratio is 20.

[0166] The porosity of the porous ultra-high molecular weight polyethylene fiber is 4.3%.

[0167] Comparative Example 4

[0168] Same as Comparative Example 3, except that light calcium carbonate is replaced by sodium chloride.

[0169] The porosity of the porous ultra-high molecular weight polyethylene fiber is 3.7%.

[0170] Comparative Example 5

[0171] The same as Example 1, except that the mass ratio of ultra-high molecular weight polyethylene: calcium carbonate: decalin is 100:40:1300.

[0172] The porosity of the porous ultra-high molecular weight polyethylene fiber is 45.0%.

[0173] Comparative Example 6

[0174] The same as Example 1, except that the acid bath is first used for dipping and then the solvent is removed. In this example, too many broken fibers can not form effective finished fibers.

[0175]

Claims

1. A coated ultra-high molecular weight polyethylene fiber, comprising a porous fiber matrix and a coating material that covers at least a portion of the surface of the fiber matrix and fills at least a portion of the holes in the fiber matrix, wherein the porosity of the porous fiber matrix is ​​5-40% (preferably 10-20%).

2. The coated ultra-high molecular weight polyethylene fiber according to claim 1, wherein the coating material comprises a filler and a resin.

3. The coated ultra-high molecular weight polyethylene fiber of claim 1, wherein the filler is selected from at least one of metal particles, metal oxide particles, ceramic particles, conductive polymer particles, nanofibers and graphene particles, preferably selected from at least one of nano iron powder and graphene particles, and its average particle size is 1-100nm (preferably 20-50nm), and / or, the resin is selected from at least one of thermosetting resins and thermoplastic resins, preferably selected from at least one of epoxy resins, unsaturated polyester resins, phenolic resin rubbers, polyurethanes, nylon resins, polystyrene resins, methacrylic resins and vinyl ester resins, and particularly preferably selected from at least one of epoxy resins and polyurethanes.

4. The coated ultra-high molecular weight polyethylene fiber of claim 1, wherein the weight of the filler is 1-60 (preferably 20-30) parts relative to 100 parts by weight of the resin, or, relative to 100 parts by weight of the coated ultra-high molecular weight polyethylene fiber, the weight of the filler is 0.1-20 (preferably 0.3-3) parts.

5. The coated ultra-high molecular weight polyethylene fiber according to claim 1, wherein the viscosity-average molecular weight of the ultra-high molecular weight polyethylene constituting the fiber matrix is ​​1 million to 9 million (preferably 3 million to 5 million).

6. A method for producing a coated ultra-high molecular weight polyethylene fiber, comprising the following steps: 1) producing a porous ultra-high molecular weight polyethylene fiber, wherein the porosity of the porous ultra-high molecular weight polyethylene fiber is 5-40% (preferably 10-20%), 2) The porous ultra-high molecular weight polyethylene fiber is immersed in a coating bath and then dried and solidified to obtain the coated ultra-high molecular weight polyethylene fiber.

7. The manufacturing method according to claim 6, wherein the step 1) comprises the following steps: 1-1) ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent are mixed to prepare a spinning solution, 1-2) extruding the spinning solution to form a spinning fine stream, 1-3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers, 1-4) stretching the dry raw yarn in one or more stages (such as 2-10 or 2-6 stages) to obtain pre-drawn yarn, 1-5) The pre-drawn filaments are immersed in an acid bath under ultrasonic or non-ultrasonic conditions to dissolve the acid-soluble inorganic particles, thereby obtaining the porous ultra-high molecular weight polyethylene fibers.

8. The manufacturing method according to claim 6, wherein in step 1-1), relative to 100 parts by weight of the ultra-high molecular weight polyethylene, the amount of the acid-soluble inorganic particles is 0.5-50 parts by weight (preferably 1-10 parts by weight), and the amount of the solvent is 100-3000 parts by weight (preferably 400-2000 parts by weight).

9. The production method according to claim 6, wherein in step 1-1), the average particle size of the acid-soluble inorganic particles is 0.02-20 μm (preferably 0.5-5 μm).

10. The production method according to claim 6, wherein in step 1-1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.

11. The manufacturing method according to claim 6, wherein in step 1-2), stretching is present or absent, and the extrusion temperature is 150-250°C (preferably 170-190°C); when stretching is present, the stretching ratio is 0-50 (preferably 2-20).

12. The manufacturing method according to claim 6, wherein in step 1-4), the operating conditions of the stretching include: The number of stretching sections is 1-10 (preferably 2-5), the stretching temperature is 90-170° C. (preferably 130-150° C.), and the stretching ratio is 2-500 (preferably 4-250).

13. The manufacturing method of claim 6, wherein in step 1-4), the dry raw silk is first pre-stretched, and then further stretched (called post-stretching) in one or more (such as 1-9 or 1-5) stages, and the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio of the post-stretching (total) is 2-50 (preferably 5-20).

14. The manufacturing method according to claim 6, wherein in step 2), the coating bath comprises a filler, a resin and a dispersion medium.

15. The production method according to claim 14, wherein the weight parts of the filler are 1-60 (preferably 20-30) and the weight parts of the dispersion medium are 1-10 (preferably 2-5) based on 100 weight parts of the resin.

16. The manufacturing method according to claim 14, wherein the filler is selected from at least one of metal particles, metal oxide particles, ceramic particles, conductive polymer particles, nanofibers and graphene particles, and its average particle size is 1-100nm (preferably 20-50nm), the resin is selected from at least one of thermosetting resins and thermoplastic resins, preferably selected from at least one of epoxy resins, unsaturated polyester resins, phenolic resin rubber, polyurethane, nylon resin, polystyrene resin, methacrylic resin and vinyl ester resin, and the dispersion medium is selected from at least one of lipids, low molecular waxes, and metal soaps, preferably selected from at least one of stearamide, paraffin, and calcium stearate.

17. The manufacturing method according to claim 6, wherein in step 2), the operating conditions of the impregnation include: Use tension porcelain pieces, under ultrasonic oscillation, the oscillation frequency is 10-70Hz (preferably 30-40Hz), the oscillation time is 1-120min (preferably 10-30min), the immersion temperature is 0-100℃ (preferably 40-60℃), the immersion time is 1-120min (preferably 10-30min), and the coating amount is 0.1%-30% (preferably 2%-5%).

18. A fabric comprising the coated ultra-high molecular weight polyethylene fiber according to claim 1.

19. A wave-absorbing composite sheet comprising the coated ultra-high molecular weight polyethylene fiber according to claim 1.